Analisis Kesulitan Membaca Permulaan Pada Siswa Dasar Kota Bekasi - Prisilia Putri; Suharjuddin Suharjuddin (Universitas Cokroaminoto Palopo, 2023)
This research was motivated by the learning difficulties experienced by class IA students at SDN Teluk Pucung VI Kota Bekasi in the initial reading material. This study is aimed to determine the ability of students for beginning reading and the types of difficulties faced by students in beginning reading. The method used in this research is a qualitative research with a case study approach. The data collection techniques used are field observation, indept interviews, and documentation. The model analysis and interpretation of data using interactive model proposed by Miles and Hubermen, namely: data collection, data reduction, data presentation, and drawing conclusions. The results showed that 6 students were able to read the beginning but still had difficulty, and 1 student could not read the beginning. The types of difficulties experienced by students include (1) difficulty distinguishing similar letters, (3) not being able to understand sound symbols, (3) having a deficiency in visual memory, (4) having a lot of reading errors, and (5) not being able to read fluent reading. Based on these results, it can be concluded that the students of class SDN Teluk Pucung VI Kota Bekasi still have difficulty reading the beginning. Collaboration between teacher and parents are needed for the sake of the students in the future time